Plant-Derived Lignocellulose Frameworks Functionalized with Silver Nanoparticles for Antimicrobial Applications - Sigdel, Anil; Sharma, Arun Kumar; Pant, Naresh Prashad; Subedi, Basanta; Oli, Hari Bhakta; Bhattarai, Deval Prasad (Sustainable Chemical Engineering, 2026)
Lignocellulosic biomaterials represent the most abundant renewable polymeric resources in nature and serve as sustainable potential alternatives to synthetic polymers due to their biodegradability, renewable sourcing, eco-friendly processing, and cost-effectiveness. In this study, cellulose, hemicellulose, and lignin were successfully extracted from the stems of Alnus nepalensis and Coriaria nepalensis and subjected to comprehensive physicochemical characterization. Quantitative compositional analysis of the biomasses revealed cellulose contents of 37% and 25.53% in Alnus nepalensis and Coriaria nepalensis, respectively. Similarly, hemicellulose yields were 8.70% and 9.41%, while lignin contents were significantly lower, with the measured values of 1.8% and 0.1% for the respective species. The extracted lignocellulosic components were characterized using chemical analysis, Fourier Transform Infrared Spectroscopy (FTIR), X-Ray Diffraction (XRD), and Scanning Electron Microscopy coupled with Energy-Dispersive Spectroscopy (SEM/EDS). Furthermore, Silver Nanoparticles (AgNPs) were synthesized and effectively incorporated within the cellulose matrix. Antimicrobial evaluation demonstrated significant inhibitory activity against the Gram-negative bacterium Escherichia coli, whereas no appreciable effect was observed against Gram-positive Bacillus subtilis. These findings underscore the potential of lignocellulosic biomaterials from these plant species for sustainable polymer applications and functional nanocomposites.